Evaluating the Shark Deterrent Effects of the Novel Exclusion Barrier in Comparison to the Rigorously Tested Sharksafe Barrier Technology - Craig P O’Connell; Julia Crews; Andre King; Juliet Gressle (Journal of Marine Science and Engineering, 2022)
Although exceedingly rare, shark attacks have a disproportionately large impact on human behavior, often resulting in shark culls. Due to the invasive nature of shark culls, innovating and testing non-invasive deterrent technologies that may minimize the potential for a rare negative shark encounter has become a conservation priority. One such mitigation approach is barriers, such as exclusion nets and the Sharksafe barrier. With both technologies exhibiting limitations and/or ineffectiveness (e.g., Sharksafe barrier), the development of a more effective technology was warranted. Therefore, this study had two key objectives: (1) to determine if DC 12 Volts 180 Newtons electromagnets can produce deterrent responses in the bull shark (Carcharhinus leucas) and (2) to determine if a newly designed and eco-friendly Exclusion barrier exhibits enhanced C. leucas deterrent capabilities when directly compared to the Sharksafe barrier. Based on 100 baited apparatus trials, electromagnetically treated baits resulted in significantly greater avoidance and reduced feeding frequencies. Furthermore, Poisson generalized linear mixed effect model analyses based on 27, 1-h trials illustrated that the Exclusion barrier region resulted in the greatest avoidance and lowest entrance and exit frequencies when compared to the control and Sharksafe barrier regions. Although the Exclusion barrier did not exclude all interacting sharks, the technology provided superior deterrent efficacy in relation to the Sharksafe barrier. Therefore, with many shark populations exhibiting precipitous declines, continued research on this novel technology on potentially dangerous shark species (e.g., white sharks—Carcharodon carcharias) and in varying ecological conditions (e.g., a high energy coastline) is warranted.